Ahab and the white whale: the contemporary debate around the forms of Catholic political commitment in Italy - Giorgi, Alberta (Democratization, 2013)
For more than the half of its republican history, the Italian political landscape was dominated by the Christian Democrats – a religiously inspired conservative political party. After its collapse, the possibility of creating a new (or renewed) Catholic party has been widely debated. This contribution focuses on how different areas of Italian Catholicism present the issue of a possible unified Catholic political commitment: what is in their opinion the unifying criterion and what shape the Catholics’ political commitment should take. Data are based on the analysis of articles from Catholic magazines and daily newspapers in the period between September 2008 and spring 2012, thus including the Monti cabinet (November 2011–February 2013).